2015
DOI: 10.1159/000375446
|View full text |Cite
|
Sign up to set email alerts
|

Midtrimester Isolated Short Femur Length as a Predictor of Adverse Pregnancy Outcome

Abstract: Objective: The aim of this study was to investigate whether midtrimester isolated short femur length is associated with pregnancy complications. Study Design: Retrospective analysis of pregnancies with a midtrimester femur length <5th percentile for gestational age compared to controls with a femur length ≥5th percentile. Outcome measures included hypertensive disorders, being small for gestational age, oligohydramnios and preterm delivery. Results: 2,105 women were eligible for this study, 85 (3.45%) of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The present meta-analysis shows that an isolated short femur increases IUGR or SGA risk fourfold in contrast with fetuses with a normal femur biometry. 1,8,9,[19][20][21] In this regard, in our study we found an increased risk for preterm birth, fetal demise, low birthweight, Apgar <7 at It should be underlined that in the case of isolated short femur, conservative counseling should be given to prospective parents because an uncomplicated pregnancy with a normal neonate at term has been reported in 61% of cases. These data support the hypothesis that an isolated short FL might be considered an early marker for placental dysfunction.…”
Section: Synthesis Of the Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…The present meta-analysis shows that an isolated short femur increases IUGR or SGA risk fourfold in contrast with fetuses with a normal femur biometry. 1,8,9,[19][20][21] In this regard, in our study we found an increased risk for preterm birth, fetal demise, low birthweight, Apgar <7 at It should be underlined that in the case of isolated short femur, conservative counseling should be given to prospective parents because an uncomplicated pregnancy with a normal neonate at term has been reported in 61% of cases. These data support the hypothesis that an isolated short FL might be considered an early marker for placental dysfunction.…”
Section: Synthesis Of the Resultsmentioning
confidence: 80%
“…In addition, a higher incidence of perinatal complication was found in fetuses with isolated short femur length: Low birthweight (study group: (Figure 9). 8,9,[19][20][21][22] In particular, we found an overall prevalence of IUGR or SGA of 14.2% in the short femur group, compared with 5.2% in the general population with an OR of 4.04 (95% CI 3.63-4.50). The present meta-analysis shows that an isolated short femur increases IUGR or SGA risk fourfold in contrast with fetuses with a normal femur biometry.…”
Section: Synthesis Of the Resultsmentioning
confidence: 96%
See 3 more Smart Citations